2002
DOI: 10.1016/s0010-938x(01)00082-8
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion behaviour of solar reflector coatings on AA 2024T3 – an electrochemical impedance spectroscopy study

Abstract: Electrochemical impedance spectroscopy in the 100 kHz±5 mHz frequency range was applied to the study of corrosion behaviour of solar re¯ector coatings on AA 2024 exposed to 3.5% NaCl solution. Solar re¯ector coatings were obtained by sulphuric acid anodization of the alloy in presence of oxo-anions of molybdenum or vanadium. Corrosion behaviour of the oxide ®lms was evaluated by determining the ®lm resistance and capacitance values with exposure time. Comparison of the results reveals that, vanadium addition c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 11 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…It means Al-5 Mg coating has a higher corrosion resistance than the Al coating after 1 h of immersion in 3.5 wt.% NaCl solution. The phase-frequency Bode plots of both coatings at high frequency reveal the oxide film formation, as has been suggested by other authors [52][53][54][55][56]. The Al-5 Mg coating exhibits around a -80° phase angle maxima at 100 kHz due to the surface properties where this coating shows dense and uniform morphology as well as a high contact angle.…”
Section: Electrochemical Impedance Spectroscopy (Eis) With Immersion ...supporting
confidence: 79%
“…It means Al-5 Mg coating has a higher corrosion resistance than the Al coating after 1 h of immersion in 3.5 wt.% NaCl solution. The phase-frequency Bode plots of both coatings at high frequency reveal the oxide film formation, as has been suggested by other authors [52][53][54][55][56]. The Al-5 Mg coating exhibits around a -80° phase angle maxima at 100 kHz due to the surface properties where this coating shows dense and uniform morphology as well as a high contact angle.…”
Section: Electrochemical Impedance Spectroscopy (Eis) With Immersion ...supporting
confidence: 79%
“…It is observed that SPCN1 and SPCN2 exhibit one time constant around −52° on 11 and 71 Hz, respectively, owing to the deposition of treatment film while AC and SPCN3 show two different time constants at different frequencies ( Figure 6a). Middle frequency attributed to the treatment/corrosion products while lower frequency shows the characteristics of the coating [34,[60][61][62][63]. The SPCN3 sample shows highest shifting in phase angle maxima at −62° on 120 Hz while at lower frequency i.e., 0.03 Hz exhibit at −13°.…”
Section: Electrochemical Impedance Spectroscopy (Eis)mentioning
confidence: 96%
“…Damage function (D) also offers important information in the corrosion behaviour of coatings. It gives a quantitative measure of degradation of impedance modulus over a period of immersion [28]. D is evaluated as follows: Corrosion current, I Corr , is calculated from anodic and cathodic Tafel slopes from the linear polarisation plots using the Stern-Geary equation given below, and results are shown in Table 3:…”
Section: Breakpoint Frequency Is Given Bymentioning
confidence: 99%
“…Equivalent electrical circuit models were developed to fit the experimental impedance data and to estimate the electrochemical parameters of porous and barrier layers [6,[15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Frequencies as low as 1 mHz were used to evaluate the barrier layer resistance and capacitance values from Bode plots in the aforementioned studies.…”
Section: Introductionmentioning
confidence: 99%